ARGAMASSAS À BASE DE GESSO COM INSERÇÃO DE ADITIVO PLASTIFICANTE - Ferreira, Davison Caíque Evangelista; Souza, José Getúlio Gomes de; Silva, Daniel Bruno Pinto da; Rodrigues, Tayná Mirelle Cavalcante (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This research aims to study gypsum mortars, analyzing the effects of plasticizer and aggregate additive contents on properties, either in the fresh or hardened state. The mortars were prepared with a water / gypsum ratio that allows immediate application after preparation, additive retarder of handle in 0.03% of the gypsum mass, plasticizer additive in the contents 0%, 0.5% and 1.0% in relation to the plaster mass and the 1: 0, 1: 1, 1: 2 and 1: 3 traces. Setting time, consistency, air content, compressive strength and tensile strength were the properties evaluated. The results of the evaluation indicate that the start and end times of the setting time were not influenced by the plasticizer additive, but reduced the second increase of the aggregate content. Nor did the consistency change with the variables. The air incorporation was minimal in the analyzed mixtures. The compressive strength reduced as the traces increased the aggregate content, as well as, in the majority, also reduced with the presence of the plasticizer. In the case of the tensile strength, all the blends exceeded 0.20 Mpa, enabling their application like inner wall coating.